Application Of Various Interactive Assessment Models To Increase The Effectiveness Of Measuring The Arabic Learning Process And Improve Learners' Skills - Rofiq Sofa, Ainur (Ukazh: Journal of Arabic Studies, 2025)
This study aims to analyze the implementation of interactive assessment models in Arabic language learning and their impact on evaluation effectiveness and students’ language skill improvement. A qualitative approach with a case study method was used in several educational institutions that have adopted interactive assessments. Data were collected through observations, interviews, and documentation, then analyzed descriptively. The assessment models examined include online quizzes, game-based tests, interactive discussions, and project-based assessments utilizing digital platforms such as Google Forms, Kahoot!, Quizizz, and iSpring Suite. The findings indicate that interactive assessments enhance students' learning motivation, engagement, and material comprehension. Additionally, this model reduces test anxiety and fosters the development of critical thinking, creativity, and collaboration skills. As an implication, educational institutions should integrate interactive assessments into the curriculum to create a more effective, enjoyable, and meaningful learning experience for students